Análisis del comportamiento de la red de energía eléctrica de distribución de la empresa ELEPCO S.A. incorporando al sistema generación distribuida mediante el software OPENDSS - Verdezoto Zurita, Brayan Steeven (2023)
This document carries out the analysis of the incorporation of distributed generation in the network of the Cotopaxi Electric Company (ELEPCO 6$.A.), with the purpose of determining the behavior of the system, before the introduction of photovoltaic systems located in the substations . The systems analyzed are of the radial type working at a level of 13.8 kV. With this intention, we start from the general single-line diagram belonging to the company ELEPCO S.A., later the modeling of the distribution system network was established in the OpenDSS software. Next, the electrical network was validated taking the simulated system in Power Factory as a reference. Once the system was validated, we proceeded to determine the points where photovoltaic systems can be introduced, for which both solar radiation and the physical space for the installation are considered.